2012
DOI: 10.1002/jcp.24042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exogenous histone H1 on rat adipose‐derived stem cell proliferation, migration, and osteogenic differentiation in vitro

Abstract: Adipose-derived stem cells (ASCs) are of great interest for the development of novel cell therapies due to their ease of isolation and expansion, immunosuppressive activity, and multilineage differentiation potential. However, the mechanisms underlying the therapeutic potential of ASCs remain to be elucidated. Others and we have shown that nuclear proteins such as histone H1 and high mobility group box 1 (HMGB1) play important roles in the maturation of dendritic cells (DCs). Furthermore, we previously demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…Hsu et al [11] found that HMGB1 promotes the osteogenic differentiation of adipose-derived stem cells and activates the ERK1/2 signal pathway, but the role of the latter in mediating the effects of HMGB1 on osteogenic differentiation was not determined. Our previous study showed that HMGB1 activates the MAPK signal pathway to promote the osteogenic differentiation of MSCs [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsu et al [11] found that HMGB1 promotes the osteogenic differentiation of adipose-derived stem cells and activates the ERK1/2 signal pathway, but the role of the latter in mediating the effects of HMGB1 on osteogenic differentiation was not determined. Our previous study showed that HMGB1 activates the MAPK signal pathway to promote the osteogenic differentiation of MSCs [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, HMGB1 has been shown to promote osteogenesis. Hsu et al [11] reported that HMGB1 promoted the osteogenesis of adipose tissue-derived stem cells. We earlier showed that HMGB1 stimulated MSC osteogenesis and migration [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of H1.0 in human ES did not affect self-renewal but impaired their differentiation. Moreover, H1 has been shown to enhance wound healing and increase interleukin -6 expressions of adult stem cells42. Thereby, H1 treatment showed an up-regulation of mitogen-activated protein kinases (MAPKs), extracellular-regulated kinase 1/2 (ERK1/2) and sequential NF-κB translocation.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were maintained in the differentiation medium for two weeks and the culture medium was replaced every 3 days [21]. For Alizarin red staining, the cells were fixed with 10% formalin and then incubated with 2% Alizarin red solution.…”
Section: Methodsmentioning
confidence: 99%